Combined liver mobilization and retraction: A novel technique to obtain the optimal surgical field during laparoscopic total gastrectomy. Issue 2 (18th December 2015) - Yoshikawa, Kozo; Shimada, Mitsuo; Higashijima, Jun; Nakao, Toshihiro; Nishi, Masaaki; Takasu, Chie; Kashihara, Hideya; Eto, Syohei
Abstract: Introduction: During laparoscopic gastrectomy, it is important to establish a good operative field and ensure an adequate working space. The combined liver mobilization and retraction method is used to get a safe and optimal view. Methods: We retrospectively analyzed 32 consecutive patients who underwent laparoscopic total gastrectomy for gastric cancer. The patients were divided into two groups: the mobilization (+) group ( n = 12) and the mobilization (−) group ( n = 20). Hepatic function tests were performed in all patients. Results: Mobilization provided a satisfactory view of the working field, especially the gastroesophageal junction and the angle of His during laparoscopic total gastrectomy, and no complications were observed during liver retraction. On postoperative hepatic function testing, there was no significant difference between the two groups on any day. Conclusions: Combined liver mobilization and retraction may be helpful in laparoscopic total gastrectomy.